Pigmented lesions in Goltz syndrome. Role played by sun exposure. - Pedicelli, C.; Angelo, C.; Cacciaguerra, M.G.; Stella, P.; Palermi, G.; Provini, A.; Paradisi, M. (European Journal of Pediatric Dermatology, 2010)
Here is reported a case of Goltz syndrome in a 14-year-old girl with multisystem lesions and characteristic cutaneous features. Besides the latter, there was a melanic hyperpigmentation, mainly located on sun exposed areas. The pathogenesis of the hyperpigmentation was discussed also in light of the literature data, underlining the opportunity of sun protection in Goltz syndrome.